Emerging Roles of Exosomes in Neuron–Glia Communication - Frühbeis, Carsten; Fröhlich, Dominik; Krämer-Albers, Eva-Maria (Frontiers in Physiology, 2012)
Brain function depends on coordinated interactions between neurons and glial cells. Recent evidence indicates that these cells release endosome-derived microvesicles termed exosomes, which are 50–100 nm in size and carry specific protein and RNA cargo. Exosomes can interact with neighboring cells raising the concept that exosomes may mediate signaling between brain cells and facilitate the delivery of bioactive molecules. Oligodendrocytes myelinate axons and furthermore maintain axonal integrity by an yet uncharacterized pathway of trophic support. Here, we highlight the role of exosomes in nervous system cell communication with particular focus on exosomes released by oligodendrocytes and their potential implications in axon–glia interaction and myelin disease, such as multiple sclerosis. These secreted vesicles may contribute to eliminate overproduced myelin membrane or to transfer antigens facilitating immune surveillance of the brain. Furthermore, there is emerging evidence that exosomes participate in axon–glia communication.